Development and Content Analysis of Lubeg (Syzygium lineatum) - Baua, Mary Ann (Plant Science Today, 2024)
The study discusses the development and composition analysis of Lubeg Vinegar. According to the Department of Agriculture Bureau of Agricultural Research, the lubeg fruit was previously an unutilized fruit. Since the fruit is easily accessible and often wasted, the researcher employed it as the primary ingredient in vinegar production. A total of 30 individuals from Isabela State University evaluated the Lubeg Vinegar. The research study utilized Mean (M) and Standard Deviation (SD). The acceptability and marketability scores of two samples of Lubeg (Syzygium lineatum) vinegar (brown sugar and white sugar) were compared using an independent samples t-test. The sizes were calculated using partial eta squared and interpreted according to Cohen's guidelines: 0.01 indicated a small effect, 0.06 a medium effect and 0.14 a large effect. Consequently, it became evident from the research that the method for making Lubeg vinegar from lubeg (Syzygium lineatum) was highly successful and efficient. Furthermore, lubeg (Syzygium lineatum) vinegar influenced consumer acceptability and was generally well-received by tasters. However, concerning color/appearance, aroma/smell, sour/acidity and respondents' willingness to purchase, Lubeg (Syzygium lineatum) vinegar with white sugar was generally more acceptable than Lubeg vinegar with brown sugar. Moreover, the commercialization of Lubeg vinegar has yielded a profitable return on investment.